Maximising system throughput in wireless powered sub-6 GHz and millimetre-wave 5G heterogeneous networks - Qazwan Abdullah; Noorsaliza Abdullah; Mohammed Balfaqih; Nor Shahida Mohd Shah; Shipun Anuar; Akram A. Almohammedi; Adeeb Salh; Nabil Farah; Vladimir Shepelev (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
Millimetre wave (mm-Wave) bands and sub-6 GHz are key technologies in solving the spectrum critical situation in the fifth generation (5G) wireless networks in achieving high throughput with low transmission power. This paper studies the performance of dense small cells that involve a millimetre wave (mm-Wave) band and sub-6 GHz that operate in high frequency to support massive multiple-input-multiple-output systems (MIMO). In this paper, we analyse the propagation path loss and wireless powered transfer for a 5G wireless cellular system from both macro cells and femtocells in the sub-6 GHz (µWave) and mm-Wave tiers. This paper also analyses the tier heterogeneous in downlink for both mm-Wave and sub-6 GHz. It further proposes a novel distributed power to mitigate the inter-beam interference directors and achieve high throughput under game theory-based power constraints across the sub-6 GHz and mm-Wave interfaces. From the simulation results, the proposed distributed powers in femtocell suppresses inter-beam interference by minimising path loss to active users (UEs) and provides substantial power saving by controlling the distributed power algorithm to achieve high throughput.